Investigating the Health Benefits Associated with the Use of Public Transport, Such as Increased Physical Activity, Reduced Air Pollution, and Improved Mental Well-Being - Rida Naz; Sajad Ahmad; Shafi Ullah; Muhammad Nadir; Muhammad Latif (Indus Journal of Social Sciences, 2023)
Background: Public transportation is to provide a cost-effective, convenient, and efficient mode of transportation for those who lack access to private vehicles or choose not to use them. Aims: To investigate the health benefits associated with the use of public transportation, including increased physical activity, reduced air pollution, and improved mental well-being. Methods: The study employed a cross-sectional design and collected data from 100 participants residing in an urban area during the year 2022. Participants’ transportation behaviors, physical activity levels, air pollution exposure, and mental well-being were assessed using questionnaires, activity trackers, and psychological assessment tools. Results: The results revealed that public transport users exhibited significantly higher physical activity levels, with an average of 9,000 steps per day (SD=1,320), compared to non-users who averaged only 1,200 steps per day (SD=231) (p<0.05). Public transport users covered an average distance of 5.2 kilometers (SD=0.87), while non-users covered only 0.9 kilometers (SD=0.09) (p<0.05). Moreover, public transport users spent an average of 57.25 minutes engaged in physical activity (SD=12.30), while non-users spent only 7.13 minutes (SD=1.10) (p<0.05). Additionally, public transport users reported spending approximately 35.12% of their time being sedentary (SD=4.76), while non-users had a sedentary behavior rate of 78.98% (SD=9.89) (p<0.05). Regarding mental well-being, public transport users had an average General Health Questionnaire (GHQ) score of 13 (SD=2), while non-users had a score of 27 (SD=5), although the difference was not statistically significant (p=0.090). Conclusion: The study findings provide evidence for the health benefits of public transportation, highlighting the potential for increased physical activity, reduced air pollution, and improved well-being among users.